Establishing quality control of oil palm suspension culture via flow cytometry, image cytometry and fluorescence in situ hybridization - Midin, Mohd Razik (2013)
Oil palm industry targets to provide high quantities of clonal palms with agronomic trait via clonal propagation of elite palms. Clonal propagation of oil palm through tissue culture process is achieved via callus or suspension cultures. The occurrence of in vitro culture stress may generate genome variability such as genome size and ploidy level alteration. Hence, several cytological tools were utilized in this study to observe any changes that might occur in adult clonal palms, their respective suspension cultures and regenerant plantlets. The tools used were flow cytometry (FCM), 18S-25S ribosomal DNA-fluorescence in situ hybridization (rDNA-FISH), and image cytometry (ICM). The findings of FCM on the nuclear genome sizes of the four adult clonal palms (using leaf samples from Frond-1) varied from 2.59±0.19 pg to 2.91±0.14 pg while for 8-months-old regenerant plantlets (five replicates for each samples) varied from 2.14±0.21 pg to 3.05±0.11 pg. Adult clonal samples and their respective regenerants showed the same ploidy level which is diploid, indicated by FCM analysis. Oil palm suspension culture materials were limited, hence produced less than 1,000 nuclei and were unable to be analysed by FCM. This led to the utilization of rDNA-FISH and development of ICM technique which used the application available in the PAX-it image analysis software (Midwest Information Systems, USA). Based on the rDNA-FISH analysis on the suspension culture and regenerant plantlet materials, two hybridization signals were observed on the interphase nuclei indicating diploid ploidy level. ICM analysis of the suspension cultures revealed that the nuclear genome size ranged from 4.71 pg to 5.49 pg while the integrated optical density (IOD) values for all suspension cultures ranged from 0.06-0.18 arbitrary unit (a.u.). The pattern showed that the cell cycle of suspension cultures was lagging during the G1-S-G2 phase, hence explaining the slow proliferation rate. In summary, it was observed that diploid ploidy state was maintained throughout the adult clonal palms, their suspension cultures and regenerant plantlets while the genome size of suspension culture materials were higher than their adult clonal palms and regenerants. This study concluded that the quality control of oil palm suspension cultures could be established by the abovementioned tools based on the estimated nuclear genome size and ploidy level. ICM tool developed in this study can also be applied to analyze the friable suspension calli cultures which are the starting material for suspension cultures. This would ensure the oil palm’s clonal fidelity and improve the efficiency and robustness of suspension cultures.